ANALISIS UNTUK MENGUKUR INDEKS KEPUASAN PASIEN DAN MASYARAKAT TERHADAP PELAYANAN PUSKESMAS KEPUTIH DI KOTA SURABAYA - Farida Idayati; Yahya Yahya (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2022)
In this study, it is intended to determine the level of patient and community satisfaction with the Keputih Health Center when using the Community Satisfaction Index and also to determine the performance carried out by the Keputih Health Center while providing health services to the community so that the vision and mission of the Keputih Health Center will be achieved, namely being able to create good health. optimal and excellent service quality to the community in its working area and make good innovations in terms of health services adapted to the situation and conditions that exist in the working area of ​​the Puskesmas. The analysis used in this research is by using a qualitative descriptive approach. Qualitative descriptive research is a researchs that explains the real conditions regarding the work of puskesmas employees in serving health to patients/communities at the Keputih Health Center. The population used in this study is an organization that is included in a public sector organization that is not for profit/non-profit, engaged in the health sector, namely the Keputih Surabaya Health Center. The object of the research is the community/patients who are being treated at the Keputih Health Center. While the research sample was obtained from incidental sampling, the sample was obtained from each patient who arrived at the Puskesmas for treatment. This study used a sample to be used as an informant/respondent with a total of 150 respondents. The results of this study indicate that for the measurement of the suitability between satisfaction and the aspirations of the community at the service at the Keputih Community Health Center as a whole, the results are 87.28%, this means that overal it is in accordance with what is expected by the patient and the community has can be served in the best possible way. The performance at the Keputih Community Health Center in providing health services according to internal data at the Puskesmas shows the quality of service that has reached the set target.